KUALITAS LAYANAN, NILAI PELANGGAN, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN KERETA API DALAM MENGGUNAKAN ACCESS BY KAI - Muhammad Sani Arsyadi; Rauly Sijabat; Rita Meiriyanti (CV. Denasya Smart Publisher, 2025)
The case study from this study found findings that showed that the Access by KAI application in October 2024 received a rating of 2.5/5.0, this value is the lowest rating of other train ticket booking applications such as Traveloka and tiket.com which received a rating of 4.8/5.0 on the play store application store, therefore the researcher wants to know